The effect of attention on the release of anticipatory timing actions - Marinovic, Welber; Cheung, F.; Riek, S.; Tresilian, J. (2014)
A loud auditory stimulus (LAS) presented during movement preparation can result in an earlier than normal movement onset. This effect had initially been assumed to be independent of the sensorial modality people attended to trigger their responses. In 2 experiments, we tested whether this assumption was warranted. In Experiment 1, we employed a timed response paradigm in which participants were cued in relation to the precise moment of movement onset of their motor responses. In the visual task, participants were cued about movement onset via visual cues on a monitor screen. In the auditory task, participants were cued about movement onset through tones delivered via headphones. During both tasks, we delivered an unexpected LAS 200 ms prior to movement onset. We found that the responses were initiated earlier by the LAS in the auditory task in relation to the visual task. In Experiment 2, we presented participants with a sequence of tones and flashes interleaved. The participants' task was to ignore either the tones or the flashes and make a movement in sync with the last tone or flash. The results showed that when participants had to ignore the task-irrelevant tones in the background, the early responses were much reduced. In contrast, when participants had to pay attention to the tones and ignore the flashes, the early release of anticipatory actions was robust. Our results indicate that attention to a specific sensorial modality can affect the early release of motor responses by LAS.